Presence of herpes simplex virus (HSV) in peripheral leukocytes of patient who developed active HSV infection after bone marrow transplantation - Roubalová, K; Suchánková, A; Vítek, A; Sajdová, J (Journal of clinical virology, 2000)
BACKGROUND: Despite of prophylactic antiviral therapy, latent HSV may be reactivated in bone marrow transplant (BMT) recipients and cause serious disease. Rapid diagnosis of HSV infection is needed to prompt institution of appropriate therapy. OBJECTIVES: We report a case of the allogenic BMT recipient, who developed ulcerative esophagitis which progressed to generalized HSV infection and graft versus host reaction (GVHR).We consider several diagnostic approaches to detection of active HSV infection in this patient. STUDY DESIGN: Polymerase chain reaction (PCR) was used to detect HSV DNA in esophageal biopsy specimens and peripheral leukocytes (PBL). Isolation of HSV in tissue culture was performed to prove infectious virus in swabs from mucocutaneous lesions or in PBL. RESULTS: Using PCR, HSV DNA was detected in peripheral leukocytes of the patient who had developed generalized HSV infection accompanied with hepatosplenomegaly and hepatitis. At that time, a fully infectious ACV-resistant HSV was isolated from his PBL. On the other hand, HSV DNA was not detected in PBL of other BMT-recipients with skin- or organ-localized infection. CONCLUSIONS: Presence of HSV-DNA in PBL of BMT recipients can signalize generalized HSV infection. Isolation of HSV from PBL by cocultivation with human fibroblasts can be used as an alternative diagnostic approach in these patients.
Keywords: Microbial Sensitivity Tests; herpes simplex; Esophagus; transplantace kostní dřeně; Biopsy; Humans; antibiotická rezistence; Leukocytes; dospělí; mikrobiální testy citlivosti; Herpes Simplex; lidé; Bone Marrow Transplantation; biopsie; Adult; Male; antivirové látky; Acyclovir; Simplexvirus; DNA virů; ezofágus; polymerázová řetězová reakce; acyklovir; Antiviral Agents; DNA, Viral; Polymerase Chain Reaction; Drug Resistance, Microbial; mužské pohlaví; leukocyty